(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals that as a result of an open, mutually beneficial and constructive foreign policy of Uzbekistan in international relations with foreign countries, strategic partnership and trade and economic cooperation have reached a completely new level.